2020
DOI: 10.1016/j.bulsci.2020.102856
|View full text |Cite
|
Sign up to set email alerts
|

Invariant ideals of local analytic and formal vector fields

Abstract: The objective of this paper is to analyse analytic invariant sets of analytic ordinary differential equations (ODEs). For this purpose we introduce semiinvariants and invariant ideals as well as the notion of vector fields in Poincaré-Dulac normal form (PDNF). We prove that all invariant ideals of a vector field in PDNF are already invariant for its semi-simple linear part. Additionally, this paper provides a natural characterization of invariant ideals via semi-invariants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The following are two main results from the doctoral dissertation [22] of N. Kruff. The proofs are too long (and a bit too technically involved) to be presented here.…”
Section: Proofmentioning
confidence: 96%
“…The following are two main results from the doctoral dissertation [22] of N. Kruff. The proofs are too long (and a bit too technically involved) to be presented here.…”
Section: Proofmentioning
confidence: 96%
“…These properties hold more generally for polynomials. An algebraic proof of this fact (which is known) is given in [19], Lemma 8.4, and we give an elementary ad-hoc proof in Sect. 1 of the Appendix.…”
Section: Lemmamentioning
confidence: 97%
“…Let Cv correspond to one of these points. Then, by Theorems 3.1 and 3.2 of [20], the local ideal defining the image of the curve under the Poincaré transform is generated by certain semi-invariants of D f * v (0), and there must be n − 1 of these, since the dimension of the curve equals one. Using property E and Lemma 3, and the fact that the transformed curve is not contained in the hyperplane {x : x n+1 = 0}, one sees that the only possible ideal is the one not containing the semi-invariant x n+1 .…”
Section: Proposition 1 Let F Satisfy Property E Then the Number Of Irreducible Invariant Algebraic Curves For System (1) Is Bounded Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some progress has been made in the area of nonlinear polynomial systems; see [15][16][17]21], and Yuno and Ohtsuka [19,20], where it is shown that methods from symbolic computation can be used to test the conditions for controlled invariance of varieties constructively. The purpose of the present work, which is in part based on the doctoral dissertations [11,17] by two authors of the present manuscript, is twofold. First, for real systems (1) there is interest not only in invariance of algebraic varieties but also in attractiveness.…”
Section: Introductionmentioning
confidence: 99%